Relationship between child-to-parent violence and cumulative childhood adversity: the mediating role of parental attachment, resilience, and emotional intelligence - Navas-Martínez, María J.; Cano-Lozano, M. Carmen (Frontiers in Psychology, 2023)
Introduction Recent research on aggressor profiles in child-to-parent violence (CPV) seems to provide promising results. However, this phenomenon has been poorly addressed in the adverse childhood experiences (ACEs) framework. This study aimed to explore the frequency of different types of ACEs and cumulative ACEs in adolescents who exert CPV, to analyze the differences between aggressors with different levels of cumulative ACEs in parental attachment, resilience, and emotional intelligence, and to evaluate the associations between these variables, as well as a possible mediational model. Methods A total of 3,142 Spanish adolescents (50.7% girls) aged between 12 and 18 years from educational centers participated. Results Adolescents who exerted CPV presented higher rates of ACEs both independently and cumulatively than those without CPV. Aggressors with cumulative ACEs (88%) in general presented more insecure parental attachment, lower resilience, and lower emotional intelligence than those without cumulative ACEs, and, in turn, aggressors with high levels of cumulative ACEs than those with low levels of cumulative ACEs. Significant associations were identified between CPV, ACEs, insecure parental attachment, resilience, and emotional intelligence. The mediation model suggested that ACEs are related to CPV through preoccupied and traumatized parental attachment and also through low levels of emotional intelligence. Discussion The findings provide a better understanding of CPV from the perspective of ACEs, especially of those cases that involve an accumulation of adverse experiences during childhood, and suggest greater professional attention to these cases with the design of specialized CPV intervention programs.